Venous interventional radiology - Findeiss, Laura K. (Thieme, 2020)
"The diagnosis and interventional management of venous disorders is a truly core area in radiology, representing a significant percentage of the caseload of an interventional radiologist-up to 75% in some institutions. Covering common disorders such as venous ulceration and varicose veins (affecting half of adults over the age of 50) as well as such serious disorders such as thromboembolic disease, this book will present the state of the art in minimally invasive diagnosis and management of these disorders. Highly practical and authoritative, this book will open with sections on epidemiology, anatomy, and the basics of venous access and then will cover the wide range of these disorders, with practical guidelines and case examples"--